Free Trade Areas and Rules of Origin : Economics and Politics - Panagariya, Arvind; Duttagupta, Rupa. (Washington, D.C. : International Monetary Fund, 2003)
Incorporating intermediate inputs into a small-union general-equilibrium model, this paper first develops the welfare economics of preferential trading under the rules of origin (ROO) and then demonstrates that the ROO could improve the political viability of Free Trade Agreements (FTAs). Two interesting outcomes are derived. First, a welfare reducing FTA that was rejected in the absence of the ROO becomes feasible in the presence of these rules. Second, a welfare improving FTA that was rejected in the absence of the ROO is endorsed in their presence, but upon endorsement it becomes welfare inferior relative to the status quo.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Mexico